Risky Futures Climate, Geopolitics and Local Realities in the Uncertain Circumpolar North - Ulturgasheva, Olga (Berghahn Books, 2022)
The volume examines complex intersections of environmental conditions, geopolitical tensions and local innovative reactions characterising 'the Arctic' in the early twenty-first century. What happens in the region (such as permafrost thaw or methane release) not only sweeps rapidly through local ecosystems but also has profound global implications. Bringing together a unique combination of authors who are local practitioners, indigenous scholars and international researchers, the book provides nuanced views of the social consequences of climate change and environmental risks across human and non-human realms.